Where they wait : a novel - Carson, Scott, 1982- (Emily Bestler Books/Atria, 2021)
"Recently laid-off from his newspaper and desperate for work, war correspondent Nick Bishop takes a humbling job: writing a profile of a new mindfulness app called Clarity. It's easy money, and a chance to return to his hometown for the first time in years. The app itself seems like a retread of old ideas--relaxing white noise and guided meditations. But then there are the "Sleep Songs." A woman's hauntingly beautiful voice sings a ballad that is anything but soothing--it's disturbing, and more of a warning than a relaxation--but it works. Deep, refreshing sleep follows. So do the nightmares. Vivid and chilling, they feature a dead woman who calls Nick by name and whispers guidance--or are they threats? And her voice follows him long after the song is done. As the effects of the nightmares begin to permeate his waking life, Nick makes a terrifying discovery: no one involved with Clarity has any interest in his article. Their interest is in him."--Amazon.